Prolonged Prothrombotic Effects of Antecedent Hypoglycemia in Individuals With Type 2 Diabetes - Chow, Elaine; Iqbal, Ahmed; Walkinshaw, Emma; Phoenix, Fladia; Macdonald, Ian A; Storey, Robert F; Ajjan, Ramzi; Heller, Simon R (Diabetes care, 2018)
Hypoglycemia has been linked to persistent increases in cardiovascular (CV) mortality in type 2 diabetes after the event. Our aim was to examine acute and downstream effects of hypoglycemia on markers of thrombosis risk and inflammation in type 2 diabetes. Twelve individuals with type 2 diabetes with no history of CV disease and 11 age- and BMI-matched volunteers without diabetes underwent paired hyperinsulinemic-euglycemic (glucose 6 mmol/L for two 60-min periods) and hypoglycemic (glucose 2.5 mmol/L for two 60-min periods) clamps on separate occasions on day 0. Fibrin clot properties, platelet reactivity, and inflammatory markers were measured at baseline, end of and after recovery from the initial clamp, day 1, and day 7 using validated assays and electron microscopy. Euglycemic hyperinsulinemia reduced platelet reactivity, decreased fibrin clot density, and improved fibrinolytic efficiency in both groups. Platelet reactivity and aggregation increased during acute hypoglycemia in both groups, resolving at recovery. In type 2 diabetes, clot lysis times and clot maximum absorbance increased up to day 7 ( = 0.002 and 0.001 vs. euglycemia, respectively), but clots from control subjects without diabetes showed limited changes. Fibrin network density increased Δ 1.15 ± 0.28 fibers/μm at day 7 after the hypoglycemic clamp ( < 0.01 for glycemic arm), whereas fibrinogen and complement C3 increased after hypoglycemia up to day 7 in type 2 diabetes only. Antecedent hypoglycemia has acute and persistent prothrombotic effects, lasting at least 7 days, that were enhanced in individuals with type 2 diabetes. These findings identify mechanisms by which hypoglycemia might increase short- and medium-term risk of CV mortality.